Exploring links between engaging customers in value co-creation and product innovativeness - Piotr Zaborek; Jolanta Mazur (International Journal of Management and Economics, 2017)
The study examines the hypothesis that firms engaging customers in value co-creation tend to display more innovativeness. As such, it is one of the few quantitative studies on the link between these two concepts. Customer engagement in value co-creation was operationalized as a multiple scale following the DART framework by Prahalad and Ramaswamy. The DART acronym denotes four salient dimensions of enabling co-creation: Dialog, Access, Risk and Transparency. The applied innovativeness metric was revenue share from new and modified products. Data were collected from 432 managers of manufacturing and service SMEs. Statistical data analysis methods included EFA, CFA and multiple regression modeling. The major finding is the existence of a significant positive effect between engaging customers in value co-creation and innovativeness. In particular, certain DART dimensions, such as Dialog, elements of Access and Risk, coincided with increased levels of innovativeness. Among the study's limitations, two are particularly pertinent. First, different conceptualizations of customer engagement in value co-creation could yield different results in terms of effect magnitudes, although the authors believe that the direction of relationships should remain the same. Second, the research considered customer engagement from the perspective of managers, which could induce bias. Hence, it may be worthwhile to examine how customers evaluate their own engagement. In terms of practical application, to enhance innovativeness, firms should intensify their efforts to engage customers in day-to-day operations. However, not all aspects of co-creation provide equal benefits - it appears that more involved actions on the part of the company are needed to produce noticeable positive effects. From a theoretical viewpoint, the findings empirically validate the business relevance of engaging customers in value co-creation. Unlike many other studies of the co-creation stream, this paper relies on a large, representative sample of manufacturing and service firms.
Keywords: L14; L15; L23; O32; 650; value co-creation; DART model; service dominant logic; innovation; SMEs